Riverbend's blogosphere: mockery and menace in colonial discourse. - Abdul Jabbar, WisamKhalid (Critical Discourse Studies, 2013)
This paper explores how Riverbend's blog/bookBaghdad burningresonates with representations of Bhabha's conceptualization of the Other through the concept of mimicry which disrupts colonial discourse. Riverbend, the pseudonym of the blogger ofBaghdad burninglaunched 17 August 2003, generates two representations of mimicry. The first is the new Iraqi governing members who, ‘hand-picked by Bremer’, represent how mimicry slips into mockery. To Riverbend, those governing members are puppets with colonial masks who project themselves as Iraqi nationalists. Their interest in Iraq is in fact a continuation of the colonial pretensions. Second, Riverbend resists the colonial discourse by utilizing mimicry as likeness with menace to both the colonizers and their mimic men. As she uses the empowering language of the colonizer as well as western humour and knowledge of pop culture to accentuate resistance, Riverbend eventually becomes a menace to the colonizer because she ‘is almost the same, but not quite’. Through the lens of mimicry as a colonial mode to legitimize authority, Riverbend becomes the voice of dissent or of resistance using cyberspace to expose both the colonizers and their mimic men as part of the ongoing colonial discourse which is both pretentious and dehumanizing.